IMPLEMENTASI SILA KETIGA PANCASILA SEBAGAI PENGUATAN WAWASAN KEBANGSAAN PADA MUATAN PPKN SISWA KELAS IV DI SDN WOJO - Pratomo, Wachid; Nadziroh, Nadziroh; Chairiyah, Chairiyah (JURNAL PEKAN : Jurnal Pendidikan Kewarganegaraan, 2022)
This study is based on the following Implementation, factors involved , content Obstacles ,Solution for Pancasila Implement the third principle of Pancasila as a national insight into civic education for student grade IV SDN Wojo. This survey is a qualitative and descriptive survey. The survey was conducted on SDN Wojo with a total of 19 fifth grade students. The data sources for this survey were the principal, fifth grade teachers, and fifth grade students. The data acquisition method used observation, interview, and documentation techniques. Survey tools are observation guides, interview guides, and documents. Test the validity of your data using a reliability test using triangulation (source, method, time triangulation). The data analysis method for this study uses Â Miles and Huberman analysis, which consists of data collection, data reduction, data display, and data validation. As a result, (1) Pancasila's Third Principles as a national insight into the content of citizens of grade IV SDN Wojo, with examples of linking citizens' learning, mutual cooperation, mutual respect of friends, tolerance, etc. Implementation was shown. Students practicing in their daily lives. -Day. (2) Support the content of grade IV SDN Wojo civic education, namely the characteristics of inclusive schools with different levels of intelligence, the implementation of Panchasila's Third Principles as a national insight into the existence of religion. Differences in factors and the existence of parental associations. (3) According to SDN Wojo, it can prove that parents lack motivation for their children. Students are not maximal in teaching Pankashira's third principle of strengthening national insights, and have limited time to teach teachers to face students. Students' faces, different attitudes and personalities. (4) To overcome obstacles in implementing Pancasila's Third Principles as a national insight into the civilian content of Grade IV SDN Wojo by providing a rating of all materials provided. Solution. Students become actions.Keywords: Implementation, Pancasila's Third Principles, Strengthening National Insights, PPKn